Photocatalytic ATRA reaction promoted by iodo-Bodipy and sodium ascorbate. Issue 10 (13th January 2017) - Magagnano, G.; Gualandi, A.; Marchini, M.; Mengozzi, L.; Ceroni, P.; Cozzi, P. G.
Abstract : Using ascorbate as a sacrificial reductant, iodo-Bodipy dye is able to promote the ATRA reaction between bromoderivatives and alkenes. Abstract : Using ascorbate as a sacrificial reductant, iodo-Bodipy dye1b is able to promote the ATRA reaction between bromoderivatives and alkenes. This finding expands the possibility of using Bodipy dyes to promote photocatalytic reactions in efficient ways.